Traitement automatique de la polysémie - Gross, Gaston (Studia Romanica Posnaniensia, 2015)
It has been an empirical fact that almost all the words are polysemous. A standard dictionary such as the Petit Robert lists 60,000 entries which correspond to 300,000 meanings. Thus, in this particular dictionary one word is paired with five different senses on average. Moreover, what is being dealt with here is no more than a general reference work, designed for a daily use. It contains only most frequent and general items, but disregards all other available meanings. In what follows, contextual properties will be demonstrated to be able to set apart each instance of polysemy, thus offering an effectual tool likely to do away with ambiguities.